An energy storage algorithm for ramp rate control of utility scale PV (photovoltaics) plants - van Haaren, Rob; Morjaria, Mahesh; Fthenakis, Vasilis (Energy (Oxford), 2015)
Balancing authorities are currently exploring options for preventing potential increases in ramping costs of conventional generators in the grid by setting ramping limits on variable energy resources. In this paper, we present the methodology and results of simulations on the smoothing performance of battery, flywheel and ultra-capacitor energy storage technologies connected to single large-scale PV (photovoltaics) plants subject to a 10%/minute ramping limit. The simulations were run using second-to-second output data of four large-scale PV plants of which two are in the Southeast of Canada (5 MW and 80 MW) and two in the Southwest of the US (21 and 30.24 MW). Energy storage units are sized for each plant on a baseline of 99% violation reductions and their performances are compared. We also present two dispatch strategies tailored to low and high cycle-life storage technologies which are modeled without forecasting measures and assuming perfect short-term forecast for the remainder of the averaging period. •Storage optimization for single large PV plants subject to a 10%/minute ramping limit.•Energy storage units are sized for each plant on a baseline of 99% violation reductions.•Study based on high (second-to-second) temporal resolution data.